2019
DOI: 10.1096/fj.201802772r
|View full text |Cite
|
Sign up to set email alerts
|

Chronic gestational hypoxia accelerates ovarian aging and lowers ovarian reserve in next‐generation adult rats

Abstract: Chronic fetal hypoxia is a common complication observed in human pregnancy, impacting pregnancies across global contexts. Exposure to chronic intrauterine hypoxia has major short- and long-term consequences for offspring health. However, the impact of chronic gestational hypoxia on female reproductive system development is unknown. We aimed to understand the impact of exposure to chronic fetal hypoxia on the developing female reproductive system. Wistar rat dams underwent normoxia (21%) or hypoxia (13%) during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…Interestingly, downregulation of genes that control DNA repair and damage response pathways may result from antecedent hypoperfusion injury before birth. The developing ovary is highly sensitive to such gestational hypoxia, with implications for the fertility of nextgeneration offspring [35][36][37]. Exposure to chronic hypoxia during fetal development accelerates ovarian aging and decreases reserve in adulthood.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, downregulation of genes that control DNA repair and damage response pathways may result from antecedent hypoperfusion injury before birth. The developing ovary is highly sensitive to such gestational hypoxia, with implications for the fertility of nextgeneration offspring [35][36][37]. Exposure to chronic hypoxia during fetal development accelerates ovarian aging and decreases reserve in adulthood.…”
Section: Resultsmentioning
confidence: 99%
“…In reconstituted ovaries derived from pluripotent stem cells, hypoxia induced oocytes to remain dormant via overexpression of Foxo3 (Shimamoto et al 2019). Hypoxia also lowers the primordial follicular reserve in rats, potentially due to a reduced capacity for DNA damage and telomere repair (Aiken et al 2019). The involvement of hypoxia also extends to the other stages of follicular development.…”
Section: F36mentioning
confidence: 99%
“…Moreover, the authors in a later job reported that the offspring, shown a reduction in the number of primordial follicles available and an increase in oxidative stress markers such as Gp91 phox and P22 phox . Therefore, prolonged exposure to fetal hypoxia causes a reduction in fertility that accelerates with the aging of the ovary [56]. However, an understanding of these molecular pathways would be necessary to develop effective interventions to protect the female offspring of a high-risk pregnancy.…”
Section: Animal Models Of Prenatal Hypoxiamentioning
confidence: 99%
“…[50] Fetal hypoxia in addition to accelerated aging of the ovary is also responsible for a reduction in fertility through an increase of oxidative stress. [56] eNOS; endothelial nitric oxide synthase, eNOS −/− mice; mice lacking the eNOS, COMT −/− mice; mice deficient in the enzyme catechol-O-methyl transferase, NO; nitric oxide, Ang II; angiotensin II, CIH; chronic intermittent hypoxia, SOD1; superoxide dismutase1, ROS; reactive oxygen species, CAT; catalase.…”
Section: Animal Models Sample Size O 2 Concentration Main Messagementioning
confidence: 99%